Enhancing Selective Photooxidation through Co–Nx-doped Carbon Materials as Singlet Oxygen Photosensitizers - Wu, Wenting; Zhang, Qinggang; Wang, Xiaokai; Han, Congcong; Shao, Xiaodong; Wang, Yixian; Liu, Jialiang; Li, Zhongtao; Lu, Xiaoqing; Wu, Mingbo (ACS catalysis, 2017)
Singlet oxygen (1O2) is considered one of the most effective and selective oxygen agents. However, it is always obtained with the help of heavy atoms in the photosensitizers to sensitize 3O2. Herein, metal–nitrogen (M–Nx) doped 1O2 photosensitizers were readily prepared from metal–nitrogen complex. Their relative metal centers (e.g., Co) chelated with the N/C moiety (Co–Nx/C) provide the primary active sites for 1O2 generation and selective oxidation. The structures of Co–Nx active sites are investigated by scanning and transmission electron microscopy and X-ray photoelectron, Fourier transform infrared, and X-ray absorption fine structure spectroscopy. Their functions for 1O2 generation are confirmed by electrons spin resonance, 1O2 emission, KSCN poisoning test, and H2SO4 etching test. These Co–Nx photosensitizers show excellent selective photooxidation abilities for 1,5-dihydroxynaphthalene after irradiation by a light-emitting diode lamp. After simple concentration and filtration, it is easy to obtain the pure product (juglone), which is confirmed by 1H NMR spectroscopy. On the basis of density functional theory calculations, metal (e.g., Co) chelated with N/C moiety, especially for the Co–pyridinic N structure, could effectively reduce the singlet–triplet energy gap (ΔE ST). It is speculated that this strategy for lowering ΔE ST could benefit intersystem crossing from the singlet state to the triplet state and efficient sensitization of 3O2 (triplet state) into 1O2 for selective photooxidation.